Plagiarism and Self Plagiarism in Occupational Health Research : Insights and Current Perspectives - Ratih Catur Sholihah (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Integrity is the most crucial element for the reputation of scientific research and publication. Plagiarism is a significant contributor to unethical publications and retractions among research in regions of Asia (namely South, East and Southeast). Self-plagiarism is a form of plagiarism. The number of scientific journals published per year has been steadily increasing, so have the occurences of plagiarism and self-plagiarism in medical research.Methods: In March 2025, we conducted basic search techniques within all fields in Cochrane, Google Scholar and Scopus. We searched PubMed using an advanced search technique with medical terms (MeSH terms). We counted sources from scientific journals published in English between 2018 and 2025.Results: Plagiarism is a prevalent type of research misconduct in which an author presents another individual’s work (such as ideas, data, results, or text) as their own, without giving credit or obtaining consent from the original source. Self-plagiarism can be found when an author duplicates text/ results from his own previous publications. There are three practical steps to avoid plagiarism: cite everything properly, synthesize, and contribute your analysis.Conclusions: Researchers can learn about different types of plagiarism (i.e. self-plagiarism) by taking appropriate training in scientific writing. They can encourage the utilization of plagiarism detection tools, resulting in a significant decrease in the issue. By synthesizing knowledge, methodologies, and perspectives from different disciplines, the risk of unintentional plagiarism can be minimized.